To Make a New Race : Gurdjieff, Toomer, and the Harlem Renaissance. - Woodson, Jon (University Press of Mississippi, 1999)
Jean Toomer's adamant stance against racism and his call for a raceless society were far more complex than the average reader of works from the Harlem Renaissance might believe. In To Make a New Race Jon Woodson explores the intense influence of Greek-born mystic G.I. Gurdjieff on the thinking of Toomer and his coterie--Zora Neale Hurston, Nella Larson, George Schuyler, Wallace Thurman--and, through them, the mystic's influence on many of the notables in African American literature. Gurdjieff, born of poor Greco-Armenian parents on the Russo-Turkish frontier, espoused the theory that man is a.